Play-based learning in practice: An exploration of early childhood education teacher’s experiences in Yogyakarta - Amir, Inevianti; Rohmadheny, Prima Suci; Purnama, Sigit; Rosada, Ulfa Danni; Maharani, Ega Asnatasia (Universitas Ahmad Dahlan, 2024)
Playing has become an effective method to holistically stimulate various aspects of child development. However, misconceptions among early childhood education (PAUD) teachers regarding the concept of Play-Based Learning (PBL) can lead to potential malpractice. Therefore, this study aims to explore the extent of PAUD teachers' experiences in Yogyakarta City in implementing PBL. Using a survey design, this research produced both quantitative and qualitative data. Data collection was conducted with the assistance of Google Forms, targeting PAUD teachers in Yogyakarta City through random sampling (N=41) using closed, semi-open, and open-ended questions. Quantitative data were analyzed using descriptive statistics, and qualitative data were analyzed using thematic analysis. The results showed that 12.2% of PAUD teachers in Yogyakarta City had low experience in implementing PBL, 56.1% were in the medium category, and the remaining 31.7% were in the high category. This condition is supported by PAUD teachers' recognition that they face a challenge in needing to have broad insights. Meanwhile, four weaknesses of teachers include the various disparity of teacher’s understanding of the PBL concept and three main skills that still require support to improve the quality of PBL implementation and overcome existing weaknesses. Therefore, the study recommends the need to facilitate the strengthening of PAUD teachers' skills tailored to their cluster needs in implementing PBL.